Essential trace metals in plant responses to heat stress. (20th November 2021) - Hendrix, Sophie; Verbruggen, Nathalie; Cuypers, Ann; Meyer, Andreas J
Abstract: Essential trace metals function as structural components or cofactors in many proteins involved in a wide range of physiological processes in plants. Hence, trace metal deficiency can significantly hamper plant growth and development. On the other hand, excess concentrations of trace metals can also induce phytotoxicity, for example via an enhanced production of reactive oxygen species. Besides their roles in plant growth under favourable environmental conditions, trace metals also contribute to plant responses to biotic and abiotic stresses. Heat is a stress factor that will become more prevalent due to increasing climate change and is known to negatively affect crop yield and quality, posing a severe threat to food security for future generations. Gaining insight into heat stress responses is essential to develop strategies to optimize plant growth and quality under unfavourable temperatures. In this context, trace metals deserve particular attention as they contribute to defence responses and are important determinants of plant nutritional value. Here, we provide an overview of heat-induced effects on plant trace metal homeostasis and the involvement of trace metals and trace metal-dependent enzymes in plant responses to heat stress. Furthermore, avenues for future research on the interactions between heat stress and trace metals are discussed. Abstract : This work provides an overview of reciprocal interactions between trace metal homeostasis and heat stress responses in plants.